2017
DOI: 10.5326/jaaha-ms-6598
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Response and Adverse Event Profile of Bleomycin Chemotherapy for Canine Multicentric Lymphoma

Abstract: Although canine multicentric lymphoma is initially responsive to multidrug chemotherapy, resistance and relapse create a need for novel chemotherapeutics. Bleomycin is an antitumor antibiotic with a minimal adverse event profile; though commonly used for human non-Hodgkin's lymphoma, its use is poorly characterized in dogs. The purpose of this retrospective case series was to describe the clinical response and adverse event profile of systemic bleomycin for canine multicentric lymphoma (n = 10). A partial resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
1
4
0
4
Order By: Relevance
“…A bleomicina é um agente produzido a partir de Streptomyces verticillus, e seu mecanismo de ação se dá, assim como nas demais antraciclinas, a partir de quebras no DNA de fita dupla (Smith et al, 2017; PUBVET v.13, n.2, a279, p.1-8, Fev., 2019 Stevens et al, 2017), além de inibir a síntese proteica a partir da inibição de RNA (Smith et al, 2017). Uma das vantagens em sua utilização se refere à baixa incidência de efeitos mielossupressivos (Smith et al, 2017).…”
Section: Bleomicinaunclassified
See 3 more Smart Citations
“…A bleomicina é um agente produzido a partir de Streptomyces verticillus, e seu mecanismo de ação se dá, assim como nas demais antraciclinas, a partir de quebras no DNA de fita dupla (Smith et al, 2017; PUBVET v.13, n.2, a279, p.1-8, Fev., 2019 Stevens et al, 2017), além de inibir a síntese proteica a partir da inibição de RNA (Smith et al, 2017). Uma das vantagens em sua utilização se refere à baixa incidência de efeitos mielossupressivos (Smith et al, 2017).…”
Section: Bleomicinaunclassified
“…É amplamente utilizada no tratamento de carcinomas de células escamosas (Klopfleisch et al, 2016); além da boa aplicabilidade em linfomas e neoplasias testiculares em cães. As doses terapêuticas do fármaco ainda não foram completamente estabelecidas em animais domésticos, no entanto, aplicações por via intramuscular ou subcutânea na dose de 0,5 U/kg provaram ser bem toleradas em cães com linfoma multicêntrico (Smith et al, 2017).…”
Section: Bleomicinaunclassified
See 2 more Smart Citations
“…Increased intracellular concentration can be obtained by electrochemotherapy and some studies reported significant clinical benefits and low side effects when bleomycin is given intralesional or intravenously in combination with electrochemotherapy [ 20 , 22 , 23 , 24 ]. Occasionally, bleomycin has also been used alone or in combination with cytarabine in relapsed canine lymphoma [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%